The Translation of Simile in Charlotte Bronte's Jane Eyre - Mohamad, Saneih A. (2016)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Saneih A. Mohamad entitled, "The Translation of Simile in Charlotte Bronte's Jane Eyre," submitted in November 2016. Thesis advisor is Dr. Sattar Izwaini. Soft and hard copy available.